2012
DOI: 10.1530/joe-12-0338
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 antagonist reduces early-stage atherosclerosis in diabetic apolipoprotein E-deficient mice

Abstract: Although it has been reported that deficiency of toll-like receptor 4 (TLR4) is associated with reduced atherosclerosis in atherosclerosis-prone mice and attenuated pro-inflammatory state in diabetic mice, it remains undetermined whether treatment with a TLR4 antagonist reduces atherosclerosis in nondiabetic or diabetic mice that have TLR4 expression. In this study, we determined the effect of Rhodobacter sphaeroides lipopolysaccharide (Rs-LPS), an established TLR4 antagonist, on early-stage atherosclerosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 32 publications
2
54
0
Order By: Relevance
“…A large body of research has demonstrated that NF-κB and TLR-4 activities are closely associated with lipid metabolism, inflammation and progression of AS [55][56][57][58]. In the absence of TLR-4, the innate immune and inflammatory responses were inhibited and atheromatous plaque sizes were diminished [59][60][61]. NF-κB is a well-known downstream effector of TLR-4, and suppression of LPS-induced NF-κB signaling attenuates atherogenesis [62].…”
Section: Discussionmentioning
confidence: 99%
“…A large body of research has demonstrated that NF-κB and TLR-4 activities are closely associated with lipid metabolism, inflammation and progression of AS [55][56][57][58]. In the absence of TLR-4, the innate immune and inflammatory responses were inhibited and atheromatous plaque sizes were diminished [59][60][61]. NF-κB is a well-known downstream effector of TLR-4, and suppression of LPS-induced NF-κB signaling attenuates atherogenesis [62].…”
Section: Discussionmentioning
confidence: 99%
“…It also inhibits vascular inflammation and atherogenesis in diabetic apolipoprotein E-deficient mice (Lu et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the link between P.g LPS-and AGEs-mediated dysregulation of cholesterol metabolism has not fully been cleared. Blocking NF-kB activation has been regarded as an efficient approach to attenuate atherosclerotic plaque formation [9,20,21], suggesting that upstream modulators in NF-kB activation might be helpful to elucidate the underlying mechanism among PRRs-mediated signaling pathways associated with the dysregulation of cholesterol metabolism. miR-146a, one member of the miRNA-146 family, is an important modulator of differentiation and function of cells in innate and adaptive immunity.…”
mentioning
confidence: 99%